Cyber Education untuk Forum RT/RW Kelurahan Tuah Madani Kecamatan Tuah Madani Pekanbaru - Syaifullah; Herdi; Febriadi, Bayu; Viranti (Indra Institute Research & Publication, 2023)
According to Pekanbaru Mayor Regulation Number 152 of 2017, one of the special requirements to become RT/RW head is having and being able to operate a smart phone. Facts on the ground can be seen in daily activities, RT/RW administrators rarely respond to information on the existing RT/RW forum WA group. If there are people who are still like that, don't know the function of the existing smart phone features, don't fully know the function of social media, especially WA which has been installed on their smart phone, don't understand or are not able to use social media as a medium for meetings, one of for example zoom meetings. Based on these two contradictory things, the PKM team has provided a solution to partners, the Tuahmadani sub-district RT/RW forum, in this case represented by the mothers of the Majlis taklim of the Nurul Ikhlas RW01 mosque, Tuahmadani sub-district, through a training activity called Cyber Eduvation for six months. . As a result, they were very satisfied with the knowledge provided, communicated smoothly via WA, and no longer worried that their Android cellphone memory would be full.